A companion to the history of science edited by Bernard Lightman - Lightman, Bernard V. 1950- (Wiley Blackwell companions to world history, 2016)
The Wiley Blackwell Companion to the History of Science is a single volume companion that discusses the history of science as it is done today, providing a survey of the debates and issues that dominate current scholarly discussion, with contributions from leading international scholars.